Comprehensive comparison of six microarray technologies - Yauk, Carole L. (Nucleic Acids Res, 2004)
Microarray technology is extensively used in biological research. The applied technologies vary greatly between laboratories, and outstanding questions remain regarding the degree of correlation among approaches. Recently, there has been a drive toward ensuring high-quality microarray data by the implementation of MIAME (Minimal Information About a Microarray Experiment) guidelines and an emphasis on ensuring public-availability to all datasets. However, despite its current widespread use and availability, very little is known about the extent to which application of the different technologies influences the outcome of transcriptional profiles and differential expression. The results among the handful of published studies are conflicting. Here, we present a comprehensive evaluation encompassing different reporter systems (short oligonucleotides, long oligonucleotides and cDNAs), labelling techniques and hybridization protocols. We used four oligonucleotide and two cDNA platforms to compare gene expression between two sample types. We determined the overall consistency (reproducibility) within each platform, and correlation among replicates within and between technologies. We find that the top performing platforms show low levels of technical variability that result in an increased ability to detect differential expression. Most importantly, we show the top four platforms are highly correlated with biological, rather than technological, differences accounting for the majority of variation in the data.